Does mean platelet volume influence the attack or attack-free period in the patients with Familial Mediterranean fever?. (June 2013) - Sahin, Safak; Senel, Soner; Ataseven, Hilmi; Yalcin, Ilker
<x xml:space="preserve">Abstract</x> Familial Mediterranean fever (FMF) is an autosomal recessive hereditary disease which is characterized by recurrent attacks of fever and peritonitis, pleuritis, arthritis, or erysipelas-like skin disease. Mean platelet volume (MPV) is a sign of platelet activation. There are limited studies in the literature about MPV levels in FMF patients. We aimed to investigate MPV levels during the attack period (group 1) and attack-free periods (group 2) in FMF patients, and to compare them with healthy controls (group 3). The study consisted of the data of: 60 group 1 patients, 120 group 2 patients, and 75 group 3 patients. Erythrocyte sedimentation rate, C-reactive protein, white blood cell count, platelet count, and MPV levels were retrospectively recorded from patient files. Statistical analyses showed that MPV was significantly lower in FMF patients both in group 1 and group 2 than in group 3 (p = 0.004, p = 0.002, respectively); however, there was no difference among group 1 and group 2 in patients with FMF (p = 0.279). The mean platelet count of group 1 was higher than that of group 3 (p = 0.010). In conclusion, this study results suggested that MPV level did not increase on the contrary, it decreased in patients with FMF both in group 1 and/or group 2 when compared to group 3. It was concluded that the lower MPV level was an expected result of secondary thrombocytosis in FMF patients.